Icings in the Selenga River basin - Vladimir Chernykh; Andrey Shikhov; Alexander Ayurzhanaev; Bator Sodnomov; Bair Tsydypov; Margarita Zharnikova; Bair Gurzhapov; Endon Garmaev; Avirmed Dashtseren (Journal of Maps)
In this study, we present a GIS dataset and map of icings formed in the transboundary Selenga River basin (largest tributary of the Lake Baikal). The GIS dataset of icings is compiled using Landsat and Sentinel-2 satellite images, as well as materials from the field expedition studies. It contains 29,054 individual icings with a total area of 1154.2 km2 (0.25% of the entire basin area), including at least 56 giant icings with an area ≥ 1 km2. Icings are widespread throughout the basin, but the highest icing coverage is found on the northern slopes of Hangayn ridge in the southeastern part of the basin, where most of the giant icings are located. The highest density of icings (more than 200 per km2) is found in the eastern part of the basin. Since icings can indicate climate-driven changes in streamflow and permafrost, the presented dataset will form the basis for future studies of these transformations.